Assessment of alcohol histories obtained from patients with liver disease: opportunities to improve early intervention. Issue 10 (18th October 2013) - Fagan, K. J.; Irvine, K. M.; Kumar, S.; Bates, A.; Horsfall, L. U.; Feeney, G. F.; Powell, E. E.
Abstract Background Alcohol is an important primary and comorbid cause of liver injury in patients referred for investigation and management of liver disease. Early assessment and documentation of alcohol consumption is therefore essential, and recommended in both general practice and hospital settings. Aims To determine the extent and accuracy of documentation of alcohol consumption in patients referred for evaluation of liver disease. Methods Patients were interviewed using a structured questionnaire. The medical records of all patients interviewed were reviewed to obtain information from the referral letter and the hepatology consultations. Results Eighty‐three patients were surveyed. Only 14 referrals had an informative alcohol history, despite 27 patients admitting risky alcohol consumption at the initial hepatology consultation. Ninety per cent of initial consultations had an informative alcohol history documented, whereas only 56% of patients attending a follow‐up appointment had informative documentation. Assessment of alcohol consumption was comparable between the hepatology consultation and the structured questionnaire, but four subjects had substantially different alcohol histories. Alcohol Use Disorders Identification Test identified all patients reporting harmful alcohol consumption on the questionnaire. Conclusions Hazardous alcohol use is prevalent in subjects attending hepatology clinics, but informative alcohol histories, which are crucial to patient management, are rarely documented in referrals. Screening tools improve documentation and accuracy of alcohol histories, and their use by general practitioners and hospital clinicians would improve detection rates of hazardous drinking and allow earlier intervention. Systematic use of screening tools in hepatology clinics will provide opportunities for education and reinforce recommendations to reduce hazardous or harmful alcohol consumption.